KEPATUHAN TERHADAP SOP KETINGGIAN PADA PEKERJA KONSTRUKSI - Fhanin Dyanita (Universitas Airlangga, 2017)
Implementing SOP (Standard and Operational Procedures) is one of the efforts to protect workers from occupational hazards, especially for high risk jobs such as working at height. The purpose of this research is to analyze factors that related the compliance of PT Sri Murni worker with working at height’s SOP in Tunjungan Plaza 6 project. This research is analytic observational with cross sectional design. The subject of this study were the sample of workers taken using simple random sampling and obtained the number of 33 respondents . The available data have been presented in the form of frequency distribution and cross tabulation, then analyzed statistically by chi square. The results showed that most workers was complianced with working at height’s SOP. The results of statistical analysis showing that knowledge (p=0,010, r=0,447) and communications (p=0,016, r=0,418) as factors that significantly related to working at height’s SOP and have moderate relations. Personality (p=0,656) and safety supervision (p=0,464) were not related to working at height’s SOP compliance. Suggestion to the company based on the results of research are to increase worker’s knowledge through safety talk or training, and the safety man to pay more attention to workers while they are doing working at height’s job so they could more compliance to SOP. Company should also provide PPE as much as the number of workers.